Adaptation and psychometric evaluation of the Young Diagnostic Questionnaire (YDQ) for parental assessment of adolescent problematic Internet use - Wartberg, Lutz; Kriston, Levente; Kegel, Katharina; Thomasius, Rainer (Journal of Behavioral Addictions, 2016)
Background and aims The surge of problematic Internet use in adolescents is a continuously growing problem across the globe. To our knowledge, to date valid questionnaire-based measurement of problematic Internet use is possible only by self-assessment. The objective for the present study was to adapt an established instrument for a parental assessment of adolescent problematic Internet use and to evaluate the psychometric properties of this questionnaire. Methods Data were collected from a representative German sample of 1,000 parents of adolescents aged between 12 and 17 years using a standardized questionnaire. To assess problematic Internet use, we adapted the established Young Diagnostic Questionnaire by rewording the items to survey a parental rating instead of a self-report ("Parental version of the Young Diagnostic Questionnaire," PYDQ). Additionally, we assessed the Internet usage time, parental monitoring, family functioning, school performance of the adolescent, and parent-adolescent conflicts. We conducted a confirmatory factor analysis based on the 8 items of the PYDQ modeled as categorical indicators and one latent factor using a robust weighted least squares estimator. We also calculated a reliability coefficient, the acceptance of the instrument, and performed correlation analyses. Results The unidimensional model showed excellent global goodness-of-fit (χ(2)/df = 1.65, RMSEA = 0.03, CFI = 0.99, TLI = 0.99) and satisfactory factor loadings (standardized values ranged from 0.60 to 0.77). We observed a reliability coefficient of 0.70, a good acceptance of the instrument, and the correlation analyses indicated the construct validity of the PYDQ. Discussion and conclusion The proposed PYDQ is a suitable instrument for parental assessment of adolescent problematic Internet use.
Keywords: Internet gaming disorder; adolescent; parent; problematic Internet use; questionnaire; validation